2008
DOI: 10.1002/med.20145
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors and antagonists of bacterial quorum sensing

Abstract: Bacteria can regulate community-wide behaviors including biofilm formation, virulence, conjugation, sporulation, and swarming motility through a process called quorum sensing. Inhibitors and antagonists of bacterial quorum sensing are important research tools and potential therapeutic agents. In this review, we have summarized recent developments in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
130
0
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 261 publications
1
130
0
8
Order By: Relevance
“…In recent past, many sources were explored for QSI, and few with the potential to inhibit various pathogens were reported from plants, synthetic chemicals and microbes [3][4][5][6][7]. Because of the increasing rate of rediscovery of known drugs from terrestrial sources, marine microorganisms have gained much attention, since many remain unexplored [8].…”
mentioning
confidence: 99%
“…In recent past, many sources were explored for QSI, and few with the potential to inhibit various pathogens were reported from plants, synthetic chemicals and microbes [3][4][5][6][7]. Because of the increasing rate of rediscovery of known drugs from terrestrial sources, marine microorganisms have gained much attention, since many remain unexplored [8].…”
mentioning
confidence: 99%
“…[86][87][88][89] Lee et al have reported that biofilm formation was inhibited by 7-hydroxyindole and 5-hydroxyindole in E. coli. 90 It has also been reported that 4-hydroxyindole, 5-hydroxyindole, 6-hydroxyindole, and isatin inhibited not only membrane vesicle production but also Pseudomonas quinolone signal (PQS) synthesis.…”
Section: Metagenomic Screening For Quorum-sensing Inhibitorsmentioning
confidence: 99%
“…The no volatile compounds with QSI properties, like some flavonoids, malyngamide (Kwan et al, 2010), S-ribosyl-Lhomocysteine analogs (Shen et al, 2006) and macromolecules (Amara et al, 2011), are not revised. For a general revision Chan et al, 2004;Dobrestov et al, 2009;Konaklieva & Plotkin, 2006;McDougald et al, 2007;Ni et al, 2009, Rasmussen et al, 2006 and the issue number 1 of 111 th volume of The Chemical Reviews are suggested.…”
Section: Quorum Sensing Inhibitors Analysismentioning
confidence: 99%